Evaluation of pyrolysis characteristics and kinetic parameters from several prospected biomass residues by thermogravimetric analysis - Pambudi, S.; Jongyingcharoen, J. S.; Saechua, W. (My University, 2024)
With fossil fuel supplies dwindling and persistent environmental concerns surrounding their consumption, biomass has emerged as a highly promising renewable energy source. Understanding the characteristics of biomass pyrolysis is crucial as it provides valuable insights and guidance for designing and optimizing the pyrolysis process. In this regard, a thermogravimetric assessment was conducted to evaluate the pyrolysis characteristics and kinetic parameters of four prospective biomass sources: Yang Na wood (Dipterocarpus alatus), palmyra palm shell, cotton stalk, and spent coffee grounds with a condition temperature range of 33 °C to 700 °C and a heating rate of 10 °C·min-1 in a nitrogen atmosphere. The kinetic parameters were evaluated using the Coats and Redfern methods, employing various reaction order models. The activation energy and pre-exponential factor were determined for the active pyrolysis stage. The results revealed that the high heating values for all samples ranged from 18.20 to 23.00 MJ·kg-1. Additionally, the onset temperature fell within the range of 243 to 254 °C, while the offset temperature ranged from 365 to 452 °C for all samples. The conversion rate at the offset temperature was 0.67 for Yang Na wood, 0.62 for palmyra palm shell, 0.65 for cotton stalk, and 0.74 for spent coffee grounds. Moreover, the activation energies were measured as 46.47 kJ·mol-1 for Yang Na wood, 52.46 kJ·mol-1 for palmyra palm shell, 64.20 kJ·mol-1 for cotton stalk, and 69.01 kJ·mol-1 for spent coffee grounds. The higher activation energy corresponded to a higher pre-exponential factor. In conclusion, the pyrolysis characteristics and kinetic parameters of the four types of biomasses have been found to be favourable, indicating their potential for promotion and application as a raw material for the pyrolysis process.
Keywords: Biomass; kinetic analysis; pyrolysis; thermogravimetric analysis